Regularities of fracture pattern formation in alumina ceramics subjected to dynamic indentation - E. Tolmacheva (Lyapunova); M. Davydova; V. Chudinov; S. Uvarov; O. Naimark; D. Zaytsev; P. Panfilov (Fracture and Structural Integrity)
In this paper the process of dynamic indentation, causing deformation and fracture of alumina ceramics, is investigated. The dynamic indentation experiments were carried out on the original setup based on the split Hopkinson bar technique. The regularities of structure evolution caused by indenter penetration are studied using the computer tomography data of the samples subjected to different loads. The investigation revealed the existence of comminuted area in the vicinity of the indenter and the formation of multiple cracks in the zone lying below. It was found that the higher is the applied indentation load, the denser is the crack pattern and larger are the cracks. A similarity of such a mechanical behavior between the examined material and dentin taken as a biocomposite is discussed.